2021
DOI: 10.3390/min11101080
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study on the Leaching of Zinc-Bearing Dust Sludge by Choline Chloride-Malonic Acid

Abstract: Molecular dynamics of the interaction between four metal oxides (ZnO, Fe2O3, Al2O3, and CaO) present in zinc-bearing dust sludge and choline chloride (ChCl)-malonic acid (MA)(1:2) was studied in this work using Materials Studio software. The interaction mechanism was revealed by analyzing the interaction energy and radial distribution function from the perspective of quantum mechanics, and the simulation results were verified by single factor leaching experiments. The calculation results show that the complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Figure 3 shows, in the YbCl aqueous solution in model a, that there are 9.0 H O molecules coordinated with Yb (III) in the first shell [35]. In addition, the coordination mode of H O molecules to cations is that the O atoms interact with the central atom or ion [36], which is a generally accepted notion. From Figure 3, it can also be observed that the RDF intensity of Cl to Yb is zero, and the coordination behavior between Yb and Cl did not occur.…”
Section: Radial Distribution Function and Coordination Behaviormentioning
confidence: 97%
“…Figure 3 shows, in the YbCl aqueous solution in model a, that there are 9.0 H O molecules coordinated with Yb (III) in the first shell [35]. In addition, the coordination mode of H O molecules to cations is that the O atoms interact with the central atom or ion [36], which is a generally accepted notion. From Figure 3, it can also be observed that the RDF intensity of Cl to Yb is zero, and the coordination behavior between Yb and Cl did not occur.…”
Section: Radial Distribution Function and Coordination Behaviormentioning
confidence: 97%
“…38 Compared to DES ChCl/Fa, the catalytic system ChCl/Fa-SnCl 4 was found to be a more robust structure with TE, DE and ZPVE of −9048.69 Ha, −56.73 kcal mol −1 and 149.23 kcal mol −1 , respectively due to the feasible interaction structures among the ChCl, Fa and SnCl 4 , which were primarily formed by coordination bonds, electrostatic interactions and Hbonds. 38,39 A charge transfer was conducted from chloride ion (Cl − ) to choline ion (Ch + ) in DES and tin ion (Sn 4+ ) in SnCl 4 . 38 The coupling Cl − in ChCl and H + in Fa was capable of forming a strong H-bond (H/Cl) similar to hydrogen chloride.…”
Section: Production Of Cyclic Alkane Fuels From Fuel Precursors By Hdomentioning
confidence: 99%